Optimalisasi Potensi Ekonomi Pesantren Melalui Usaha Ritel Pada Annuqayah Mini Market Guluk-Guluk Sumenep - hana al ithriyah; Nuril Kamiliyah; Isti'anah halimi (Jurnal Ilmiah Ekonomi Islam, 2022)
The high rate of poverty, unemployment, and the lack of employment opportunities are very crucial problems in Indonesia. The Indonesian economy is still facing serious basic problems. Relying on government performance and work programs alone will not be enough to solve this problem. It takes an institution or agency that helps to solve the problems of the Indonesian economy. Pesantren come to help developing and empowering the Indonesian economy. Currently, Pesantren is not only educational institutions, but can also actively contribute to the socio-economic life of the community. This is proven by the success of several retail businesses owned by pesantren. Besides being able to support the economy of the pesantren, the economic potential of the Pesantren through retail businesses can also help the economy of the surrounding community with the concept of community empowerment. Pesantren also benefit from the existence of learning media for students in entrepreneurship, both in terms of leadership, management, financial regulation, and so on. From these various advantages, the economic potential of Pesantren can be categorized as very useful and contribute in Indonesian economy. So it would be better if the pesantren economy was optimized in order to improve the national economy. This study seeks to reveal the economic potential of Pesantren through retail businesses in order to improve and develop the Indonesian economy. The optimization effort starts from the implementation of marketing strategies, including management of promotion, branding, physical evidence, and products. This is important to do because it has not been implemented in the AMM store. A company will progress and develop if it continues to make improvements and innovations. If not, then the company will not be able to compete and survive in the midst of an increasingly rapid market development. Improvements in management, strategy, and communication at the AMM Store should be done. This is important to do considering that they have not realized the implementation of management and marketing strategies to the fullest. In fact, the potential of the AMM store which is in the middle of a large Islamic boarding school is one of the potential market shares.